Effect of Replacement of Fishmeal With Lima Bean Meal on the Zootechnical Performances of African Catfish (Clarias Gariepinus) in the Batié Sub-Division, West Region of Cameroun - Emile, Miégoué; Pégis, Davy Tagning Zebaze; Fernand, Tendonkeng; Jules, Lemoufouet; Nadège, Elvire Njoh; Ronald, Komguep Nganyo; Et, Etienne Tedonkeng Pamo (International Journal of Aquaculture Research and Development, 2018)
This study was conducted to evaluate the effect of the substitution of fishmeal by Lima bean flouron the growth performance, survival rate and feed cost of Clariasgariepinusbetween March and May 2018 within the AIO ICG of the Batié District. It also aimed to contribute to the development of alternative sources of animal protein on a global scale. For this purpose, 300 fry of Clariasgariepinuswith an average weight of 3 ± 1.41g were divided into five batches and fed three times a day with rations corresponding to 5% of their ichthyobiomass. The rations R0, R25 R50, R75 and R100 respectively corresponded to the substitution rates of 0, 25, 50, 75 and 100% of fish meal by that of Lima bean. The physic-chemical characteristics of the water (pH, temperature, dissolved oxygen, nitrites and nitrates) were measured daily. The following results were obtained: The highest weight gains were obtained with the rations R25 (20.56 ± 0.40 g), R50 (20.64 ± 0.32 g), R75 (20.98 ± 0.46 g) and the lowest with the rations of R100 (16.21 ± 0.28 g). The highest average daily gain were 0.36 ± 0.02 g; 0.37 ± 0.01 g ; 0.38 ± 0.01 g respectively for the R0, R50 and R75 rations and the lowest with R100 (0.29 ± 0.01 g). The highest value of the specific growth rate (2.47 ± 0.07%) was obtained with the ration R0 and the lowest (1.61%) with the ration R100. The consumption index reached its highest and lowest values with the rations R100 (4.74 ± 0.42) and R50 (3.57 ± 0.43) respectively, compared to the value of the ration R0 (3.31 ± 0.37) for this parameter. Concerning the condition factor K, the highest value was recorded with the R50 diet (1.11 ± 0.49) while the lowest value was obtained with the R75 diet (0.95 ± 0.45). The cost of producing one kilogram of food was higher with the R25 ration (504.59 FCFA) and lower with the R100 ration (443.20 FCFA). Our results revealed that incorporating 75% Lima bean flour into the feed increases the growth performance of Clariasgariepinus fry and reduces the cost of food production.
Keywords: Clariasgariepinus; production cost; Lima bean; fish meal; growth